DNA Repair and Cancer Therapy: Targeting APE1/Ref-1 Using Dietary Agents. (10th September 2012) - Raffoul, Julian J.; Heydari, Ahmad R.; Hillman, Gilda G.
Abstract : Epidemiological studies have demonstrated the cancer protective effects of dietary agents and other natural compounds isolated from fruits, soybeans, and vegetables on neoplasia. Studies have also revealed the potential for these natural products to be combined with chemotherapy or radiotherapy for the more effective treatment of cancer. In this paper we discuss the potential for targeting the DNA base excision repair enzyme APE1/Ref-1 using dietary agents such as soy isoflavones, resveratrol, curcumin, and the vitamins ascorbate and α -tocopherol. We also discuss the potential role of soy isoflavones in sensitizing cancer cells to the effects of radiotherapy. A comprehensive review of the dual nature of APE1/Ref-1 in DNA repair and redox activation of cellular transcription factors, NF- κ B and HIF-1 α, is also discussed. Further research efforts dedicated to delineating the role of APE1/Ref-1 DNA repair versus redox activity in sensitizing cancer cells to conventional treatment are warranted.